Farmacocinética de S-(+)-linalol em jundiás (Rhamdia quelen) - Bianchini, Adriane Erbice (2021)
S-(+)-linalool is found in essential oils of aromatic plants as Lippia alba. This phytochemical had its sedative/anesthetic activity elucidated in Rhamdia quelen, popularly known as silver catfish. Thus, S-(+)-linalool has become an option as an anesthetic for aquaculture, but its pharmacokinetic profile was unknown until the development of this thesis. Therefore, the objective of this research was to determine the pharmacokinetic profile of S-(+)-linalool in silver catfish. S-(+)-linalool was quantified in plasma, tissue and water (from recovery) samples using gas chromatography with flame ionization detector (GC-FID). For blood and tissue collection, fish (n = 6, for each collection time) were exposed to an immersion bath with S-(+)-linalool (153 mg/L or 180 μL/L) for a maximum of 30 min (0.5 h) and after were transferred to aquariums without the anesthetic. The blood and brain samples were collected at different times in an interval from 0 to 4 hours and the other tissues (kidney, liver, gills and muscle) were collected in the interval from 0 to 24 hours (from the beginning of exposure to the anesthetic). To determine S-(+)-linalool excretion in the water another fish group (n = 6) was anesthetized as previously described and transferred to individual aquariums for up to 48 h. Water samples were collected during this period and later analyzed by GC-FID. The results found indicated that S-(+)-linalool is rapidly absorbed and distributed to the main tissues. The maximum concentrations (Cmax, tissues μg/g and plasma μg/mL) occurred in the magnitude: kidneyplasmabrainlivergillsmuscle (143.15, 129.33, 113.92, 110.03, 54.49 and 20.76, respectively) in 0.5 h (Tmax) with the exception of the brain (0.33 h). The S-(+)-linalool elimination occurs more quickly in the plasma, followed by the liver, kidneys, gills, muscle and brain (T1/2β: 1.36, 3.45, 6.30, 9.96, 11.04 and 57.27 h, respectively). Despite the slow elimination in the brain, all animals recovered from anesthesia within 10 min. Muscle was the second tissue with the highest T 1/2β, however the residual concentrations after 12 hours of clearance were less than the acceptable daily intake (500 μg/kg bw) determined for linalool (considering an intake of 300 g of tissue per a 60 kg person). The S-(+)-linalool excretion rates in water after 0.5, 1, 2, 6 and 24 h of recovery were 85.10 ± 9.83, 52.45 ± 5.01, 22.67 ± 2.10, 5.62 ± 0.55 and 1.63 ± 0.05 mg/kg h, respectively. About 68% of the total S-(+)-linalool excreted occurred in the first 2 h of recovery, and no volatile metabolites were found at concentrations quantifiable by the method used. Finally, the results of this research provide a scientific basis to guide a future application of S-(+)-linalool as an anesthetic in aquaculture and, mainly, bring evidence that anesthesia (for a prolonged period) with S-(+)-linalool in this species does not cause bioaccumulation at concentrations potentially harmful to human health. However, further pharmacokinetic and toxicological studies must be developed so that this phytochemical can be used with total safety in aquatic species used for human consumption.